Sports nutritionists' perspectives on enablers and barriers to nutritional adherence in high performance sport: A qualitative analysis informed by the COM-B model and theoretical domains framework. Issue 18 (17th September 2019) - Bentley, Meghan RN; Mitchell, Nigel; Sutton, Louise; Backhouse, Susan H
ABSTRACT: Athlete adherence to nutritional guidance is critical for optimal health and performance, yet little is known about the barriers and enablers to athletes' dietary behaviours within high-performance sport. To advance understanding, we applied a theoretical lens derived from the Capability, Opportunity, Motivation – Behaviour (COM-B) model and the Theoretical Domains Framework (TDF) to explore the qualitative accounts of sports nutritionists. Five focus groups comprising sports nutritionists working in Olympic and Paralympic sport (n = 14), professional sport (n = 6), or both (n = 6) were undertaken. Thematic analysis was conducted and the interpretations of the findings were guided by COM-B and the TDF. To achieve nutritional adherence, the behavioural analysis identified the need to intervene across all three COM-B components and at least five associated TDF domains (e.g., decision-making processes, reinforcement, social influences, behavioural regulation and environmental context and resource). For the first time, the findings illustrate the complex interplay of the training setting with the capabilities, opportunities, and motivation of the practitioners, athletes and coaches. By applying established behavioural science theories to sports nutrition, the foundations for the development of targeted and multifaceted behavioural interventions addressing athlete dietary adherence in high-performance sport have been laid.